Kinetic Adsorption of Direct Yellow Onto Zn/Al and Zn/Fe Layered Double Hydroxides - Neza Rahayu Palapa; Bakri Rio Rahayu; Tarmizi Taher; Aldes Lesbani; Risfidian Mohadi (Science and Technology Indonesia, 2019)
Zn/Al and Zn/Fe layered double hydroxides has successfully synthesized by co-precipitation methods with molar ration 3:1. The samples were characterized using X-Ray Diffraction, Fourier Transform Infrared Spectroscopy and Surface Area using BET method. In this study, Zn/Al and Zn/Fe layered double hydroxides were used to remove direct yellow dye in aqueous solution. The experiments were carried out time variations with the aim of observing the kinetic studies. The results showed that the adsorption of direct yellow onto Zn/Al and Zn/Fe layered double hydroxides based on co-efficient correlation kinetic models more fit using pseudo-second-order than pseudo-first-order.